KARAKTERISTIK DEMOGRAFI, PENGETAHUAN DAN KECEMASAN PASIEN STROKE - AMILA, AMILA; SEMBIRING, EVARINA; SAMOSIR, GLORIA BETARIA; MUNAWARAH, SITI (Jurnal Online Keperawatan Indonesia, 2025)
Stroke is one of the leading causes of morbidity and mortality in the world, including in Indonesia. In addition to physical impacts, stroke can also cause psychological disorders, such as anxiety, which can affect the patient's recovery process. The patient's level of knowledge about stroke plays an important role in managing this disease. Demographic factors, such as age, gender, education level, and socioeconomic status, can affect the level of knowledge and anxiety of patients about stroke. Objective: This study aims to analyze the relationship between demographic characteristics and the level of knowledge and anxiety in stroke patients at RSUP Haji Adam Malik Medan. Methods: This study used a descriptive analytical design with a cross-sectional approach. The study sample consisted of 135 stroke patients selected using a purposive sampling technique. Data collection was carried out through a questionnaire that measured demographic characteristics, level of knowledge about stroke, and patient anxiety levels. Data analysis was carried out using the chi-square test to determine the relationship between variables. The results showed that 18 people (13.3%) aged <39 years had knowledge in the good category (3.7%), sufficient category (3.7%), and poor category (5.9%). Of the (45.5%) aged 40-59 years had knowledge in the good category (11.1%), sufficient category 37 people (27.4%) had knowledge in the poor category 6.7%). Of the (41.5%) aged 60-79 years had knowledge in the good category (5.9%), sufficient category (12.6%), and poor category (23.0%). there was a significant relationship between demographic characteristics and the level of knowledge and anxiety of stroke patients (p <0.05). Conclusion: Demographic characteristics have an influence on the level of knowledge and anxiety of stroke patients. It is recommended to explore other factors that may influence anxiety in stroke patients and assess the effectiveness of educational programs in improving patient understanding of this disease.